2013
DOI: 10.1364/oe.21.011322
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria species identification by the statistical analysis of bacterial colonies Fresnel patterns

Abstract: It was demonstrated that statistical analysis of bacteria colonies Fresnel patterns recorded in the optical system with converging spherical wave illumination is suitable for highly effective bacteria species classification. The proposed method includes Fresnel patterns recording followed by image processing and the statistical analysis based on feature extraction, feature selection, classification and classification performance methods. Examination performed on various bacteria species (Salmonella enteritidis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…In addition, the proposed method can also be integrated in a portable platform for field measurements when it combines with in-line holography37. Both biological studies and biomedical applications, such as label-free species identification1738 of food pathogens, are expected to be further facilitated by the proposed aFTLS approach for measuring the 2D ALS patterns of individual bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the proposed method can also be integrated in a portable platform for field measurements when it combines with in-line holography37. Both biological studies and biomedical applications, such as label-free species identification1738 of food pathogens, are expected to be further facilitated by the proposed aFTLS approach for measuring the 2D ALS patterns of individual bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In some restricted cases, the image processing can even provide a reliable bacteria identification, nevertheless this approach cannot be applied to a significant number of pathogens. The optical forward-scattering (OFS) 3 technique, that has been proposed as a label-free method for bacterial identification (Banada et al, , 2009Bae et al 2011b; Suchwalko et al 2013) is also based on image processing, but in this case the identification is done at the colony level and, under suitable conditions, it has been demonstrated that the colony can provide a reliable signature of the constituting bacterium at the serotype level (Rajwa et al 2006;Akova et al 2010;Buzalewicz et al, 2011). The OFS technique has been mainly investigated in the foodsafety field, however, due to its great potential its usage also in the clinical laboratory is worth to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the ability of these instrumental analytical techniques to obtain reliable and accurate results in the identification and classification of microorganisms, the use of digital images presents some advantages, since it has low-cost equipment, avoids the manipulation of the Petri plate where microorganisms are grown, and does not require the knowledge of a skillful microbiologist. In this sense, some works concerning image analysis have been proposed in the literature [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Suchwalko et al [21] identified bacteria species (Salmonella enteritidis, Staphylococcus aureus, Staphylococcus intermedius, E. coli, Proteus mirabilis, Pseudomonas aeruginosa, and Citrobacter freundii) based on their colonies' Fresnel diffraction patterns recorded in an optical system with converging spherical wave illumination. The proposed method used image processing and statistical analysis based on feature extraction, feature selection, and classification methods, reaching 98 % identification accuracy in 36 h from sample acquiring.…”
Section: Introductionmentioning
confidence: 99%